Arc Thermal Spray NiCr20 Alloy Coating: Fabrication, Sealant, Heat Treatment, Wear, and Corrosion Resistances - Van Tuan Nguyen; Quy Le Thu; Tuan Anh Nguyen; Quoc Cuong Ly; Ly Pham Thi; Ha Pham Thi; Thanh Dinh Thi Mai (International Journal of Electrochemistry)
This study presents the effect of heat treatment on porosity, phase composition, microhardness, and wear and corrosion resistances of the thermal sprayed NiCr20 coating after sealing with aluminum phosphate. The annealing temperatures were varied in a range of 400 to 1000°C. The obtained results indicated the porosity of coating decreased with increasing the annealing temperature. After treatment at temperatures in range of 800-1000°C, more than 90% of initial pores in the coating were successfully filled with the sealants. The XRD data revealed not only the formation of new phases of other compounds, but also the interaction between coating and sealant. After heat treatment, wear resistance of coating was 12 times higher than that without heat treatment. The corrosion test in H2SO4 solution indicated that the presence of sealant in coatings increased their corrosion resistance. From these findings, application of these NiCr20 coatings to protect steel against wear and corrosion appears very promising.